Avaliação de política de educação especial: estudo de caso da Escola José Martins Rodrigues em Maracanaú/CE - Oliveira, Káthia Cyléa Meneses de (2024)
The aim of this study is to present an analysis of the Special and Inclusive Education Policy, based on the perceptions of the management team, teachers and parents, as well as to identify strategies for improving this policy. Specifically, to describe the actions that are being developed from the perspective of Special and Inclusive Education at the JosÈ Martins Rodrigues School; to investigate the main difficulties encountered by teachers and the school's management team in fully implementing the inclusive education policy; and to identify strategies for improving this policy. In this way, we decided to carry out a qualitative study, whose procedures are guided by a case study, documentary, field, exploratory and in-depth evaluation type of research, given that the answers are reached through the development of techniques that allow us to measure and count the patterns and relationships between the characteristics of the object of research. The subjects' perception of the Special Education Policy from the perspective of Inclusive Education in the municipality of Maracana˙, in general, is a positive one, as they see it as a "reference", "as an opportunity for everyone to participate in the teaching learning process equally". And they still see the municipality as being ahead of others, although they do highlight the various problems that are still latent in everyday school life, especially funding, infrastructure and structure, and teacher training.